PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP KUALITAS PELAPORAN KEUANGAN DAERAH (Studi pada Badan Keuangan Daerah Kabupaten Sukoharjo) - Anggita Fitriana, Ayu Nanda Riski; Widarno, Bambang; Harimurti, Fadjar (Universitas Slamet Riyadi, 2019)
This research aims to know the influence of the capacity of human resource, utilization on onformation tecnology and accounting internal control to quality of local gonverment financial reprter. The object to this reseach in the service revenue financial mangemen sukoharjo local goncerment. This type of research is a survey of regional financial a agency sukoharjo local gonverment. The number of respondents who participated in this research is 84 employes. The date analysis techique used ins mutiple linear regression, t test, F test, and R2. Analysis with the help of SPSS 21 program. The result of the reserach are the capacity of human resource, utilization on onformation tecnology influences significantly positive to quality of local gonverment financial reporter, homever accounting internal controlis not influences significantly to quality of lokal gonvermen financial reporter.